From stigma to statute: unpacking the concept of menstrual leave in the Indian socio-policy landscape - Mary T., Beaulah Mercy; Pritika; Sharma, Shreya; Th, Rameshwori; R., Selvi; Chetanmala Devi, Khumbongmayum; Kavitha, Gadhi; R., Yashodamma; Suhashini; Shanmugam, Yamunadevi; P. F., Regina; Umar, Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The concept of menstrual leave has emerged as a pivotal intersection of gender equity, labour rights, and public health in India’s evolving socio-policy landscape. Despite its growing visibility in corporate and legislative spaces, the idea remains conceptually fragmented and socio-culturally contested. This concept analysis, conducted using Walker and Avant’s eight-step framework, critically deconstructs menstrual leave to identify its defining attributes, antecedents, consequences, and conceptual boundaries. Through a systematic review of scholarly articles, legal documents, corporate policies, and policy briefs sourced from PubMed, Scopus, and SSRN, the study elucidates menstrual leave as a rights-based, inclusive, and physiologically grounded policy construct. Key findings highlight menstrual leave’s defining features-its explicit linkage to menstruation, symbolic recognition of bodily integrity, and its dual nature as both a welfare provision and an equity instrument. Antecedents such as menstrual stigma, workplace absenteeism, and feminist advocacy were found to shape its emergence, while consequences include enhanced wellbeing, gender-sensitive workplaces, and risks of stereotype reinforcement. The analysis further delineates surrogate terms like “period leave” and “menstrual rest,” and constructs model and contrary cases to clarify conceptual limits. Ultimately, menstrual leave represents more than a health accommodation-it signifies a shift from silence to recognition, from stigma to statute. Anchored in sustainable development goals (SDG 3, 5, and 8), this paper advances the discourse on menstrual equity, inclusive labour policy, and gender-responsive governance in contemporary India.